Dry machining of inconel 718 - Leong, Ceng Yew (2016)
Dry machining has been gaining interest from the industry due to the concern of machining cost and effects on environment. This method has not been commonly applied in industry which the cutting material is nickel-based superalloy that has low machinability. Besides that, the quality of work is of high concern as well, which dry machining might not be able to achieve due to less lubrication and cooling effect. Currently, there is no experiment on dry turning of Inconel 718 which investigates the effect of cutting speed on surface roughness, hardness, vibration, cutting temperature, cutting force, chip formation and tool wear together. In this project, all these results were obtained and studied. Five different cutting inserts were chosen to perform turning on Inconel 718 without coolant using computer numerical control (CNC) cutting machine. The experimental results showed that dry machining using coated carbide insert had the best results at a cutting speed of 100 m/min. Besides that, the insert that had a two-step chip breaker was better for dry cutting. To improve on the experiment, other cutting parameters can be considered. Furthermore, the best conditions can be used to perform dry and minimum quantity lubrication (MQL) and compare the results.